Merdeka Curriculum implementation at Granada Islamic Integrated and Dhuhaa Islamic Junior High School in Tangerang City - Dinda Adiesty Kusumawardani; Lenny Sapitri; Mia Roosmalisa Dewi (Universitas Pendidikan Indonesia, 2022)
The main support for achieving the goals of quality Indonesian human development is education. The implementation of quality education always demands transformation in every process and stage, this is because there are always dynamic constraints and problems that arise due to various situations and conditions. As a form of innovation in improving the quality of Indonesian education, Kurikulum Merdeka is implemented which has characters and characteristics that are believed to be able to answer the challenges of education in the 21st century in creating a quality generation of Indonesians. The research in this article is aimed at finding out the application of the Independent Curriculum in the learning process. in schools at the junior high school education unit level which is the Sekolah Penggerak. The research was conducted using a case study method with a convergent mixed methods approach. The results of the study show that the teachers at the Sekolah Penggerak have made optimal efforts in developing the learning process in accordance with the various core elements of the Kurikulum Merdeka. Abstrak Pendukung utama bagi tercapainya sasaran pembangunan sumber daya manusia Indonesia yang bermutu adalah pendidikan. Penyelenggaraan pendidikan yang bermutu selalu menuntut transformasi di setiap proses dan tahapannya dengan berbagai situasi dan kondisi yang selalu berubah. Sebagai bentuk inovasi dalam meningkatkan mutu kualitas pendidikan Indonesia, diberlakukan Kurikulum Merdeka yang dikembangkan memiliki karakteristik yang diyakini dapat menjawab tantangan pendidikan di abad 21. Beberapa sekolah yang siap melaksanakan Kurikulum Merdeka, kemudian menjadi Sekolah Penggerak agar dapat menjadi praktik baik bagi sekolah lainnya. Penelitian bertujuan untuk mengetahui penerapan Kurikulum Merdeka dalam proses pembelajaran di sekolah pada tingkat satuan pendidikan SMP yang merupakan Sekolah Penggerak. Penelitian dilakukan dengan metode studi deskriptif dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa para guru di Sekolah Penggerak sudah berupaya optimal dalam mengembangkan proses pembelajaran sesuai dengan berbagai elemen inti dari Kurikulum Merdeka. Mulai dari kepala sekolah, guru, tenaga pendidik dan pemangku kepentingan lainnya sudah bekerja sama dan berkoordinasi dengan baik agar penyelenggaraan Kurikulum Merdeka dapat terlaksana dengan optimal. Kata Kunci: implementasi kurikulum; Kurikulum Merdeka; Sekolah Penggerak